“Nossa Senhora Aparecida: a nova Padroeira do Brasil” - diálogos sobre a devoção popular e a romanização - Tonetti, Julio César Minga (2019)
This dissertation presents a study on the institutionalization of the popular devotion to Our Lady Aparecida made by the Catholic Church of Brazil during the process of Romanization. Its purpose is to analyze the instrumentalization of devotion as a political strategy used by it. At the end of the 19th century the Church of Brazil began an attempt to "romanize" popular devotions, seeking to strengthen their unity through rituals and celebrations. The main Marian devotion in this period was the cult of Our Lady Aparecida, recognized as the principal patroness of Brazil by Pope Pius XI in the year 1930. According to popular tradition told by the Church, the "encounter" of the image would have occurred around the year of 1717 in the region of Guaratinguetá-SP. The image that was found by three fishermen became an icon of veneration and became popular with the spread of his miracles. This devotion crossed several historical periods of national politics and was officially made on May 31, 1931, in the city of Rio de Janeiro (federal capital in the period) in a religious and civic ceremony led by Cardinal Archbishop D. Leme with the other Brazilian bishops. In this ceremony Our Lady Aparecida was proclaimed the principal Patroness of Brazil "romanizing" according to the canons of the Church this popular devotion